2008
DOI: 10.1179/106698108790818639
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Movements of the Sacroiliac Joint: A Systematic Review of the Literature and Assessment of Clinical Utility

Abstract: The high frequency of static and dynamic palpation methods used during evaluation of SIJ problems in clinical practice demands an understanding of the factual quantity of movement at the SIJ. The objective of this systematic literature review was to synthesize three-dimensional (3-D) motion of the sacroiliac joint (SIJ) during various functional static postures and movements and to determine the clinical utility of movement during examination. A computer-based search was performed by means of OVID, which inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 29 publications
(42 reference statements)
2
50
0
3
Order By: Relevance
“…Second, a potential source of error in our model is that the actual movement of interest exceeds ROM in our phantom. All clinical RSA studies describe small movements in the SI joint [5,[16][17][18][19][20]. In these studies, a maximum rotation of 3.6°is seen and the translation never exceeds 2 mm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, a potential source of error in our model is that the actual movement of interest exceeds ROM in our phantom. All clinical RSA studies describe small movements in the SI joint [5,[16][17][18][19][20]. In these studies, a maximum rotation of 3.6°is seen and the translation never exceeds 2 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Different radiographic modalities have been used to measure movement in the sacroiliac (SI) joint objectively [7,12,15], whereas five studies have used RSA to evaluate movement between the sacrum and the ilium [16][17][18][19][20]. With RSA, a maximum rotation of 3.6°has been measured and the translation never exceeded 2 mm in the SI joint, which is less movement than other methods have revealed [5], and for this reason the method has been questioned [3]. Despite the use of pelvic RSA in clinical research, the accuracy and precision have not been fully evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…These are very large numbers relative to some very conservative contemporary estimates of sacroiliac mobility, such as those of Sturesson et al [31][32][33] and those appearing in a review article by Goode et al 34 However, the 1.5 in of artificial LLI created by Pitkin and Pheasant is also very large compared with the amount of LLI produced or found in other studies herein reviewed, some of which showed a linear, monotonic dose response of pelvic torsion to induced LLI. Moreover, the mean amount of torsion reported by them is within shouting distance of other modern investigators who have reported far more torsion to occur, such as a clinical study by Cibulka et al, 35 a cadaveric study using advanced imaging by Smidt et al, 36 another clinical study by Smidt et al, 37 and the Drerup and Hierholzer 20 study included in this review.…”
Section: Study Observationsmentioning
confidence: 89%
“…We now know that a wealth of evidence exists that suggests that palpation-based tests are not reliable or valid, during the diagnostic process for sacroiliac joint syndrome. [14][15][16][17] If one looks at this without emotion, it makes good sense; the movements are minute, 18 the joints are covered with excessive amounts of soft tissue and fat, and other diagnoses (that are typically more prevalent) such as low back pain will yield positive findings on palpation tests (findings are not unique to the sacroiliac joint). 19 Nonetheless, clinicians still advocate their use as diagnostic measures because they see changes in patients when they perform an intervention that is targeted to the sacroiliac joint.…”
Section: Palpation Tests Of the Sacroiliac Joint Are Diagnostic For Smentioning
confidence: 99%